Inequality and the Financial System - The Case of Germany - Daniel Detzer (International Labour Organization (ILO), 2014)
This paper examines the relationship between changes in the financial sector and the increasing inequality in Germany. For this, first an overview about the development of the main inequality indicators for Germany is given, which show inequality has been rising since the 1980s. Thereafter, the main features of the German financial system and its main changes in the last decades are reviewed. It is also looked at employment and incomes in the financial sector to determine, whether exorbitant growth of the financial sector, as observed in other countries, could be responsible for the increasing inequality. Thereafter, the relation of the financial sector with the non-financial sector is examined. First, a look at the financing structure of non-financial firms is taken. Subsequently, it is studied how changed behaviour in the financial sector may have led to increased inequality. It is argued that a multitude of factors including the retreat of the big banks from the German Inc., the changes in securities market regulation, the occurrence of new types of financial investors have all changed the corporate governance system in a way that made it more conducive to inequality. Then, the most important regulatory reforms and reform proposals for the financial sector are outlined. In the last section of the paper the main results are summarised and some general conclusions are drawn.
Keywords: 330; financial system; income distribution; wage differential; employment; financial sector; bank; Germany